Integral inequalities and stability of an equilibrium state on a time scale - Luk’yanova, T. A.; Martynyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present some integral inequalities on a time scale and establish sufficient conditions for the uniform stability of an equilibrium state of a nonlinear system on a time scale.